KAJIAN BUDAYA PREMANISME DAN DAMPAKNYA TERHADAP KENYAMANAN PENGUNJUNG (STUDI KASUS DI KAWASAN PESISIR PANTAI CAROCOK, PESISIR SELATAN, SUMATERA BARAT) - Levani Disi Ayunda; Fauzana Annova (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research explores the phenomenon of thuggery at Carocok Beach, Pesisir Selatan, West Sumatra, and its impact on visitor comfort. Using a narrative review method, this research collects and analyzes data from various literature sources to provide a comprehensive picture of the culture of thuggery and its effects. The research results show that thuggery in this coastal area is characterized by acts of extortion, intimidation and physical violence by certain individuals or groups, which not only disturbs local residents but also disturbs the comfort of tourists. The impacts include a decrease in the number of tourists, a negative image of the area, economic losses, diversion of tourist destinations, reduced investment, and psychological impacts on tourists. This research recommends strict law enforcement, community empowerment, improving infrastructure quality, and socio-economic programs as strategic steps to overcome thuggery and support sustainable tourism development on Carocok Beach